Reaksi Pasar Atas Pengumuman Stock Split - Putra, Putu Gede Aditama; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi, 2019)
Every corporate action carried out by a company has the potential for information content as signal. The purpose of this study is to reexamine the market reaction to the announcement of the stock split proxied by using abnormal return. Testing information content will be done by looking at the cumulative abnormal return significance. The method of determining the sample is by nonprobability purposive sampling technique. The data analysis technique used was the One Sample t-test. The results of this study indicate there is a market reaction to the announcement of the stock split. This is indicated by the existence of abnormal returns around the announcement of the stock split. The results of this study theoretically can provide empirical evidence that strengthens the signaling theory that the information published by the issuer is reacted by the market, which shows that any accounting information that enters the capital market has information content. Keywords : Stock split, abnormal return.